(untitled) (Bangladesh Heart Journal, 2017)
Aortic sclerosis (ASc) is defined as thickening or calcification of the aortic valve without significant obstruction of blood flow. Aortic sclerosis is diagnosed when in echocardiography, thickening and calcification of one or more cusps of a tricuspid aortic valve is manifested, whereas in aortic stenosis, cusp separation is restricted and the velocity through the aortic valve is > 2.5 m/s. Its prevalence increases with age. Aortic valve stenosis is associated with systemic endothelial dysfunction, and it carries a 50% increase in risk of cardiac death or myocardial infarction. As aortic sclerosis has proved to be more and more relevant in recent days, it has been important to identify epidemiological data and demographic information of aortic sclerosis in Bangladeshi population. This study tried to determine age distribution of aortic sclerosis in Bangladehsi population. Median age of aortic sclerosis patients was 65 years (mean 67 ± 12 years), most of the patients (17.2%) were in 56-60 years of age group. The same statement holds correct for females, where highest number of patients (7.7% of total patients) were in the same age group. For the males, the highest number of patients (11% of total patients) were in 61-65 years of age group. The minimum age was 45 years for both males and females. Although the minimum age is same for both sex, females are affected a bit earlier than males, and statistically significant difference was found between mean ages of two sexes. Most of the aortic sclerotic patients are below the usually used age cut off of 65 years. There is significant difference between mean age of presentation of aortic sclerosis between males and females. Further study should be undertaken to understand these effects more clearly. Bangladesh Heart Journal 2017; 32(1) : 50-54